Chromosomal site-specific double-strand breaks are efficiently targeted for repair by oligonucleotides in yeast - Storici, Francesca (National Academy of Sciences, 2003)
The repair of chromosomal double-strand breaks (DSBs) can be accomplished through homologous recombination in most organisms. We report here that exogenous oligonucleotides can efficiently target for repair a single DSB induced in a chromosome of yeast. The efficiency of recombinational targeting leading to a desired DNA change can be as high as 20% of cells. The DSB was generated either by a regulatable I-SceI endonuclease just before transformation or appeared spontaneously at the site of a long inverted repeat composed of human Alu sequences. The approach used features of our previously described delitto perfetto system for selecting transformants with integrative recombinant oligonucleotides. The DSB repair mediated by pairs of complementary integrative recombinant oligonucleotides was efficient for targeting to homologous sequences that were close to or distant from the DSB and in the presence of a competing homologous chromosome in diploid cells. We also demonstrate that a DSB can strongly stimulate recombination with single-stranded DNA, without strand bias. These findings expand current models of DSB repair. In addition, we establish a high-throughput system for rapid genome-wide modification with oligonucleotides.